Antimony oxide based glasses - Nalin, Marcelo [UNESP]; Poulain, M.; Ribeiro, SJL; Messaddeq, Younes [UNESP] (Elsevier B.V., 2001)
Glass formation has been investigated in binary systems based on antimony oxide as the main glass former: (100-x)Sb2O3-xWO3, (5 < x < 65), (100 - x)Sb2O3-xSbPO(4), (5 < x < 80) and (100 - x)Sb2O3-x[Sb(PO3)(3)](n), (10 < x < 40). Ternary systems derived from the Sb2O3-WO3 binary glass have also been studied: Sb2O3-WO3-BaF2 Sb2O3-WO3-NaF and Sb2O3-WO3-[Sb(PO3)(3)](n). Glass transition temperature ranges from 280 degreesC to 380 degreesC. It increases as the concentration in tungsten oxide or antimony phosphate increases. Refractive index is larger than 2. Tungsten-containing glasses are yellow in transmission and turn green at the largest WO3 content. Optical transmission and temperatures of glass transition, T-g, onset of the crystallization. T-x, and maximum of crystallization, T-p, have been measured using differential scanning calorimetry (DSC). These glasses have potential photonic applications. (C) 2001 Elsevier B.V. B.V. All rights reserved.